Game-Changing Innovations for Food System Transformation: Evidence on Women’s Inclusion in Livestock Vaccines Systems in Northern Ghana - Njiru, Nelly; Galiè, Alessandra; Omondi, Immaculate A.; Omia, Dalmas; Loriba, Agnes; Awin, Peter (International Livestock Research Institute, 2023)
There has been considerable debate on how to develop gender-equitable agri-food innovations. Much of the debate is on whether gender-accommodative approaches (GAAs) and the more-recent gendertransformative approaches (GTAs) can work and how. Evidence on best pathways for gender-equitable agri-food innovations is limited. Livestock contributes to animalsource foods and to progress toward gender-equitable agri-food systems. Gender inequality reduces women’s access to productive resources, including livestock vaccines, with negative consequences on livestock productivity and women’s empowerment. We present results of a systematic assessment of interventions by a development project—the Women Rear—and their contribution to change in gender norms, access to livestock vaccines, and women’s empowerment (WE). Qualitative data were collected from 25 single-sex and one mixed focus group discussions (FGDs) and 39 key informant interviews (KIIs) with different value chain actors to assess changes in gender norms that limit women’s ability to access livestock vaccines and their empowerment, after the GT and the GA interventions. Resulting from GTAs, the restrictive gender norms started to relax. Prior to the project, women were not allowed to own livestock, state in any context that they owned them and sell them. Now they can do all three things (albeit at different degrees). Men appreciate that these changes reduced men’s financial burden. Women’s empowerment and critical consciousness are positively associated with changes in gender norms. We recommend pathways toward more-inclusive livestock research and innovation that contribute to women’s empowerment and healthy livestock for inclusive agrifood systems.